The Influence Of Leadership Style And Work Discipline On Employee Performance (Census Of Civil Servants At The Department Of Cooperatives, Micro, Small And Medium Enterprises, Industry And Trade, Tasikmalaya City): - Rinjani, Rijan; Rahwana, Kusuma Agdhi; Asyiah, Ai Kusmiati (Journal of Management, Economic, and Accounting, 2024)
The research aims to determine the simultaneous and partial influence of Leadership Style and Work Discipline on Employee Performance in Civil Servants at the Department of Cooperatives, Micro, Small and Medium Enterprises, Industry and Trade, Tasikmalaya City. This research method uses quantitative research methods with descriptive methods. The respondents in this research were 54 civil servant employees at the Tasikmalaya City Department of Cooperatives, Micro, Small and Medium Enterprises, Industry and Trade. The type of data used in this research is primary data obtained through a questionnaire. The data testing technique used in this research uses validity tests, reliability tests and classical assumption tests. Data analysis in this research used multiple regression analysis tools using SPSS version 25 software. Data collection techniques used literature studies, interviews, questionnaires. The research results show that Leadership Style and Work Discipline simultaneously have a significant effect on Employee Performance. Leadership style partially has a significant effect on employee performance. Work Discipline partially has a significant effect on Employee Performance.